Condition and level of damage to mangrove ecosystems in Birem Bayeun and Rantau Selamat Districts - Fahmi, Rizal; Yulianda, Fredinan; Yulianto, Gatot (Acta Aquatica: Aquatic Sciences Journal, 2025)
East Aceh Regency is one of the many regencies that have experienced a decrease in area in the last 27 years due to the conversion of mangrove land into pond areas or other interests. Banyuen and Rantau Seulamat Districts are also among the districts that have experienced a decrease in area until 2014. Areas that have abundant resources can be threatened by human activities. This requires appropriate ecosystem management to maintain the sustainability and sustainability of resources. This study aims to see the current condition of the mangrove ecosystem. The sampling method used is purposive sampling, with 3 mangrove data collection stations. then the density level and the level of damage will be analyzed. The results of the study showed that there has been an increase in the area of ​​mangroves in the Birem Bayuen and Rantau Seulamat Districts by 846.03 hectares from 2014 to 2023. The types of mangroves found were Rhizophora apiculata, Avicennia alba, Sonneratia caseolaris, and Nypa fruticans. There are various types of biota such as fish, crabs, birds, shrimp, molluscs and reptiles. The mangroves in Birem Bayuen and Rantau Seulamat Districts have a density level of "Very Dense", with the number of individuals 31 Ind/m2, and has a relatively very low level of deterioration. This area is still far from significant damage, but the local community is massively carrying out mangrove felling activities to be used as building materials and firewood or charcoal. It is necessary to carry out appropriate sustainable ecosystem management, one of which is conservation-based ecotourism activities. Keywords: Damage; Density; Management, Mangrove